Pengaruh Substitusi Tepung Ubi Jalar Orange Terhadap Kualitas Cookies - Humairah, Uttri; Elida, Elida; Gusnita, Wiwik (Journal of Home Economics and Tourism, 2017)
This study aimed to analyze the effect of substitution of orange sweet potato flour as much as 25%, 50%, and 75% of the quality of shape, color, aroma, texture and flavor to cookies. Pure experimental research type (true experiment) with a completely randomized design method. The dependent variable quality of the cookies by using primary data sourced from five expert panelists by asking the organoleptic test format. Data were analyzed by ANOVA and if influential continued with Duncan test. The study states that Ha accepted (F count> F table (6.0)), which means there is a significant influence on the quality of cookies aroma, texture quality (fragile, small pores) cookies, the quality of taste (sweet potato orange) cookies and H0 rejected meaning that there is no significant effect on the quality of the form (neat, uniform, florals six petals) cookies, cookies color quality taste qualities (sweet) cookies with orange sweet potato flour substitution.Keywords: Substitution, Sweet Potato Flour Orange, Quality, Cookies